A Long Non-coding RNA IVRPIE Promotes Host Antiviral Immune Responses Through Regulating Interferon β1 and ISG Expression - Zhao, Lingna; Xia, Min; Wang, Keyu; Lai, Chengcai; Fan, Hongxia; Gu, Hongjing; Yang, Penghui; Wang, Xiliang (Frontiers in Microbiology, 2020)
Accumulating studies have shown that long noncoding RNAs (lncRNAs) modulate multiple biological processes, including immune response. However, the underlying mechanisms of lncRNAs regulating host antiviral immune response are not well elucidated. In this study, we report that analysis of the existing dataset transcriptome blood immune cells of patients with IAV infection and after recovery (GSE108807) identified a novel lncRNA, termed as IVRPIE (Inhibiting IAV Replication by Promoting IFN and ISGs Expression), was involved in antiviral innate immunity. In vitro studies showed that IVRPIE was significantly upregulated in A549 cells after IAV infection. Gain-and-loss of function experiments displayed that enforced IVRPIE expression significantly inhibited influenza A virus (IAV) replication in A549 cells. Conversely, silencing IVRPIE promoted IAV replication. Furthermore, IVRPIE positively regulates the transcription of interferon β1 and several critical interferon-stimulated genes (ISGs), including IRF1, IFIT1, IFIT3, Mx1, ISG15, and IFI44L, by affecting histone modification of these genes. In addition, hnRNP U was identified as an interaction partner for IVRPIE. Taken together, our findings suggested that a novel lncRNA IVRPIE is a critical regulator of host antiviral response.